Developing Design Criteria for Sustainable Urban Parks - Didem Dizdaroglu (Journal of Contemporary Urban Affairs, 2022)
This study investigates how urban parks can contribute to helping cities become more sustainable through developing a set of criteria for the sustainable design of urban parks. Today, there is no example around the world where all the proposed sustainable design criteria are applied together in a specific urban park. In this context, this study aims to make a novel contribution by systematically reviewing the literature on the sustainable design of urban parks. In the light of research findings, this study contributes to the implementation of a comprehensive sustainable park design practice in our cities in the future. These design criteria may further serve as performance indicators to offer information and know-how to local authorities, practitioners, communities, and other actors in this field to help them assess their success levels and progress over time.